Staging of Osteochondral Lesions of the Talus: MRI and Cone Beam CT. Issue Volume 101:Issue S2(2017) (16th December 2017) - Posadzy, Magdalena; Desimpel, Julie; Vanhoenacker, Filip
Osteochondral lesions (OCL) of the talus involve both articular cartilage and subchondral bone of the talar dome. This term refers to a wide spectrum of pathologies including mild bone marrow contusion as well as severe osteoarthritis resulting from long standing disease. Although Magnetic Resonance Imaging (MRI) at 1.5 Tesla is the leading cross-sectional modality for detection and staging of OCL, lack of spatial resolution hampers accurate assessment of thin articular cartilage. Cone Beam Computed Tomography (CBCT) arthrography is better suited for precise staging of cartilage lesions. The purpose of this pictorial review is to illustrate the strength of each imaging method.